The effectiveness of strength-based training on students' academic performance - Parsakia, Kamdin; Darbani, Seyed Ali; Rostami, Mehdi; Saadati, Nadereh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: One of the basic issues and problems of the educational life of people and the educational system of any country is the issue of academic decline and the low level of academic performance of the students of that country. Therefore, the aim of the research was to investigate the effectiveness of strength-based training on students' academic performance. Methods: The present research was quasi-experimental with an experimental group and a control group and a pre-test, post-test design. For this purpose, 16 people were selected from the statistical population of undergraduate students of Islamic Azad University of South Tehran Branch (Valiasr Complex) by random sampling and randomly assigned to two experimental (8 people) and control (8 people) groups and their academic performance Evaluated. These people participated in Smith's (2004) strength-based training sessions individually in 10 90-minute sessions. The data were analyzed using the univariate analysis of covariance test using SPSS statistical analysis software. Results: The findings showed that academic performance (P